Synthesis of Aminobismuthanes via Me3SnCl Elimination. Issue 21 (21st June 2017) - Schulz, Axel; Thomas, Max; Villinger, Alexander
Abstract : The synthesis of N ‐trimethylstannylamines of the type R N(SnMe3 )H (stannylated anilines) with the sterically encumbered substituents R such as Ter [terphenyl, 2, 6‐bis(2, 4, 6‐trimethylphenyl)‐phenyl], Ar* [2, 6‐bis(diphenylmethyl)‐4‐methylphenyl], and Mes* (supermesityl, 2, 4, 6‐tri‐ tert ‐butylphenyl) is described. These stannylated anilines were treated with BiCl3 leading to the formation of R N(H)BiCl2 (for R = Ter), ( R NH)3 Bi (for R = Mes*), and R N(BiCl2 )2 (for R = Ar*). The synthesis and structure of the starting material R N(SnMe3 )H and the new aminobismuthanes are reported. Abstract :